A phase‐shift modulated series resonant converter achieving zero‐voltage and zero‐current switching for wide output voltage range battery charging applications. Issue 16 (22nd July 2022) - Liang, Yanke; Liu, Xu; Lyu, Shixuan
Abstract: In this article, a phase‐shift modulated zero‐voltage and zero‐current switching (ZVZCS) series resonant converter (SRC) was proposed for constant current (CC) and constant voltage (CV) charging operating at the series resonant frequency. Wide output voltage range is achieved by adjusting the duty cycle of the primary inverter for CC charging and unity gain is for CV charging at full duty cycle. By tuning resonant tank parameters, discontinuous conduction mode (DCM) and boundary conduction mode (BCM) are obtained in CC charging and CV charging, respectively, which ensures zero‐current switching (ZCS) of rectifier diodes and nearly ZCS of leading leg in whole charging profile. Meanwhile, a constant triangular current provided by a novel auxiliary circuit is used to implement zero‐voltage switching (ZVS) for all primary MOSFETs with a reduced conduction loss. The auxiliary current is independent of duty cycle and load variation. Compared with the conventional ZVZCS phase‐shift full‐bridge converter with capacitive output filter, smaller conduction loss and turn‐off loss can be obtained in battery charging profile. Detailed circuit operation principles and model analysis are presented. A 100 kHz/1 kW prototype is built to verify the performance.